Biomass—A Renewable Resource for Carbon Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Grateful thanks are given to Dr. Fouad El Monsouri and coworkers for contributing Chapter 1, which deals with ground water contamination with nitrate. Thanks are due to Dr. Arcadius Martininen Agassin Ahogle and coworkers for contributing Chapter 2, dealing with the assessment of soil organic carbon. Grateful thanks are provided to Dr. Puttapati Sampath Kumar and coworkers for contributing Chapter 3, dealing with the exploitation of eucalyptus leaves for electrode fabrication in supercapacitors. Indebtedness is due to Dr. Almaz S Jalilov and coworkers for contributing Chapter 4, dealing with the production of activated carbon from petroleum waste (vacuum residue). Thanks are due to Dr. Yongdan Li and coworkers for contributing Chapter 5, dealing with the use of exhausted olive pomace for the production of fuel for direct carbon fuel cells (DCFC). Grateful thanks are due to Dr. Roberta Mota-Panizio and coworkers for Chapter 6, dealing with the development of a concept for the production of essential oils and biomethane from biomass waste. Thanks are due to Dr. Vitali Nitsenko and coworkers for contributing Chapter 7, dealing with the modelling studies on the yield of biogas from organic mass. Thanks are due to Dr Imane Moulefera and coworkers for contributing Chapter 8, dealing with the adsorption of atenolol. Grateful indebtedness is due to Dr. Denis Mirohnichenko and coworkers for contributing Chapter 9, dealing with the development of bioedegradable polymer gels. Finally, indebtedness is due to Dr. Steven C Peterson and coworkers for contributing Chapter 10, dealing with the production of porous and polar biochar for composite applications.